PENGARUH RENDAM KAKI DENGAN AIR HANGAT TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL - ulya, Fitria hikmatul (EMBRIO, 2019)
Soaking feet with warm water can result in vasodilation in the blood vessels that caused the bloodstream to run smoothly so the muscle can be relaxed. In Kudus Regency, the rate of the anxiety of pregnant mothers approaching the birth date is 44,2%. Purpose: To know the effect of feet soaking with warm water toward the stress level of pregnant mothers in the third trimester around the Puskesmas Jati region. The type of research is using the pra experiment with one group pretest-posttest research design. The sample of this research is 16 pregnant mothers in the third semester around the Puskesmas Jati region in February of 2019. The technique to gather the sample is using purposive sampling. Soaking feet with boiled water for 10cm – 15cm deep for 20 – 30 minutes. The average rate of anxiety before is about 61,75 (hard anxiety) while after the treatment is about 54,13 (medium anxiety). The effect of feet soaking with warm water to the third-semester pregnant mother is p-value 0,033 with a different rate of 7,62. The pregnant mother hopefully can reduce the anxiety level by soaking their feet in warm water.